Ferrofluid plug as valve and actuator for whole-cell PCR on chip - Lok, Khoi Seng (2012)
Ferrofluid plug was first used as valve and actuator to circumvent the evaporation of aqueous fluid in LOC. Moreover, this dynamic plug catered for aqueous fluid expansion during its heating in the microchannel. Whole-cell polymerase chain reaction (PCR) protocol was successfully implemented in a magnetically actuated closed-loop PCR microchip system. Here, the ferrofluid plug was used to reduce the evaporation of the PCR sample in the thermal lysis step. A whole-cell PCR model was used to demonstrate this concept. The DNA plasmid, pUC19, was transformed into DH5α competent cells. Primer pairs were designed to amplify region of interest in pUC19. The transformants were cultured and selected. Whole-cell PCR was performed on intact bacteria to screen for the presence of pUC19, containing the region of interests. Serial dilutions demonstrated the limit of detection for this system to be four bacterial cells. PCR amplifications were verified with regular thermocyclers and results were comparable.